The unemployment factors among fresh graduates / Sharifah Sofia Syed Redzuan - Syed Redzuan, Sharifah Sofia (Faculty of Business and Management, 2019)
Recently, the Bank Negara Malaysia (BNM) reported in the annual report (2018) that the starting salary for fresh graduates had been lower in 2018. This phenomenon could have led to unwelcome issues such as unemployment among fresh graduates. This situation also has led to an anxiety feeling among the society as the marketability of the fresh graduates become decrease from year to year. Thus, a study has been conducted by the researcher in order to find out the relationship between those variables with unemployment. This study is aimed to test the relationship between lack of skills, lack of employability skill and person job mismatch with unemployment among the fresh graduates. About 132 of the respondents that has been involved in this study which is the final year student UiTM KBM. The data that has been collected in this study are been analyzed by using IBM SPSS statistic software. The descriptive statistic was used to measure the relationship between lack of skills, lack of employability skill and person job mismatch with unemployment among the fresh graduates. The result indicated that there is a positive relationship between lack of skills, lack of employability skill and person job mismatch with unemployment among the fresh graduates. The discussion of study implications and future research will be explained at the end of this study.